Cushing’s Disease: Assessment of Early Cardiovascular Hemodynamic Dysfunction With Impedance Cardiography - Jurek, Agnieszka; Krzesiński, Paweł; Gielerak, Grzegorz; Witek, Przemysław; Zieliński, Grzegorz; Kazimierczak, Anna; Wierzbowski, Robert; Banak, Małgorzata; Uziębło-Życzkowska, Beata (Frontiers in Endocrinology, 2021)
Background Cushing’s disease (CD) is a rare condition associated with a high cardiovascular risk and hypercortisolemia-related hemodynamic dysfunction, the extent of which can be assessed with a novel noninvasive method, called impedance cardiography (ICG). The standard methods for hemodynamic assessment, such as echocardiography or ambulatory blood pressure monitoring may be insufficient to fully evaluate patients with CD; therefore, ICG is being currently considered a new modality for assessing early hemodynamic dysfunction in this patient population. The use of ICG for diagnosis and treatment of CD may serve as personalized noninvasive hemodynamic status assessment and provide a better insight into the pathophysiology of CD. The purpose of this study was to assess the hemodynamic profile of CD patients and compare it with that in the control group. Material and methods This observational prospective clinical study aimed to compare 54 patients with CD (mean age 41 years; with 64.8% of this population affected with arterial hypertension) and a matched 54-person control group (mean age 45 years; with 74.1% of this population affected with arterial hypertension). The hemodynamic parameters assessed with ICG included the stroke index (SI), cardiac index (CI), systemic vascular resistance index (SVRI), velocity index (VI), acceleration index (ACI), Heather index (HI), and thoracic fluid content (TFC). Results The CD group was characterized by a higher diastolic blood pressure and a younger age than the control group (82.9 vs. 79.1 mmHg, p=0.045; and 41.1 vs. 44.9 years, p=0.035, respectively). ICG parameters in the CD group showed: lower values of SI (42.1 vs. 52.8 ml/m2; p≤0.0001), CI (2.99 vs. 3.64 l/min/m2; p≤0,0001), VI (42.9 vs. 52.1 1/1000/s; p=0.001), ACI (68.7 vs. 80.5 1/100/s2; p=0,037), HI (13.1 vs. 15.2 Ohm/s2; p=0.033), and TFC (25.5 vs. 27.7 1/kOhm; p=0.006) and a higher SVRI (2,515 vs. 1,893 dyn*s*cm-5*m2; p≤0.0001) than those in the control group. Conclusions CD is associated with significantly greater vasoconstriction and left ventricular systolic dysfunction. An individual assessment with ICG may be useful in CD patients in order to identify subclinical cardiovascular complications of chronic hypercortisolemia as potential therapeutic targets.